Incidence of and Risk Factors for Post‑Operative Urinary Retention Following Surgery for Perineal Tears Among Ugandan Women: A Prospective Cohort Study - Kayondo, Musa; Byamukama, Onesmus; Ainomugisha, Brenda; Kajabwangu, Rogers; Kalyebara, Paul Kato; Tibaijuka, Leevan; Lugobe, Henry Mark; Geissbühler, Verena (International Urogynecology Journal, 2024)
Introduction and Hypothesis: We aimed to determine the incidence and risk factors for post-operative urinary retention (POUR) following surgery for perineal tears, and to determine the time to normal voiding after POUR. Methods: This was a prospective cohort study of women who underwent surgery for old (≥ 3 months) obstetric perineal tears from January 2022 to December 2023. The diagnosis of POUR was made in a woman who completely failed to void despite a full bladder or, one who had post-void residual (PVR) > 150 ml within 10 min of voiding. Return to normal voiding was considered if a patient with POUR had two consecutive PVRs of ≤ 150 ml. Descriptive analyses and multivariable logistic regression were performed to determine risk factors for POUR. Results: A total of 153 participants were enrolled in this study with a mean age of 35.9 (SD ± 10.8) years. The incidence of POUR was 19.6% (30/153, 95% CI 14.02–26.7), and the median time to normal voiding for these patients was 42.4 h (range 24–72). Risk factors for POUR included repeat perineal tear surgery (RR = 4.24; 95% CI 1.16–15.52; p = 0.029) and early urinary catheter removal (RR = 2.89; 95% CI 1.09–7.67; p = 0.033). Conclusion: Post-operative urinary retention following surgery for perineal tears is common. The time to return to normal voiding in patients with POUR is short. Women having repeat perineal tear surgery and those in whom the urinary catheter is removed early were more likely to experience POUR. Delayed urinary catheter removal could be considered, especially in patients undergoing repeat perineal tear surgery.
Keywords: Perineal tears; Post-operative urinary retention; Risk factors; Surgery; Post-void residuals